Quality of Academic Administration Services at the Faculty of Social Sciences Gorontalo State University: Analysis with the SERVQUAL Model - Rahman H. Lahabu; Asna Aneta; Juriko Abdussamad; Irawaty Igirisa; Fenti Prihatini Tui; Rustam Tohopi (Cita konsultindo, 2026)
Academic administration services are a central element in supporting the smooth educational process in higher education because it is the entrance to all student academic activities. This study aims to describe the quality of academic administration services at the Faculty of Social Sciences, Gorontalo State University using the SERVQUAL model. The research approach is qualitative with interview, observation, and documentation techniques. The results show that the reliability and physical evidence of the service are good, but responsiveness, reassurance, and empathy need to be improved especially in periods of high workload. The research recommends optimizing SOPs, increasing human resource capacity, and digitizing services to improve the quality of academic administration services.